Structural behaviour of air-inflated beams. (January 2023) - Liu, Ping; Yue, Ma; Zhe Feng, Shu; Ngamkhanong, Chayut
Abstract: Inflatable structures have been proposed for many applications because they are constructed of lightweight fabric skins that enclose a volume of pressurised air and are easy for transportation and construction. This structure differs fundamentally from the conventional structures made of construction materials, and thus, the structural behaviour cannot be solved by a general theory of structures. This paper is the first to address the influence of air pressure on the structural behaviour of an air-inflated beam. The effects of beam length and loading conditions were also considered. The experiments, with several measurement sensors including an air pressure sensor and displacement sensors, were rigorously performed. After loading, the air pressure increases slightly with a continuous load increase. We found that different loading conditions created a similar deformed shape of the air-inflated beam, as the loads transformed into the fixed end moment, which was then plotted against beam deformation. According to the analytical solutions derived in this study, the pressure change significantly affected the structural behaviour of the air-inflated beam. This was demonstrated by the results of rigorous experiments that agreed well with the derived analytical solutions. Interestingly, wrinkling was observed when it reached the nonlinear stage. The beam returned to its original length after unloading with no permanent deformation, but with wrinkles, completely different from other construction materials. Therefore, in this paper, we propose a novel analytical solution to predict the deformation of air-inflated beams.